#### Question

Solve : 7y = -3y^{2} - 4

#### Solution

(1) 7y = -3y² -4

∴ 3y² + 7y + 4 = 0

Here a = 3, b = 7, c = 4

∴ y = `(-b +- sqrt(b^2 - 4ac))/2a`

=`(-7+-sqrt(449-48))/6`

=`(-7+-sqrt(1))/6`

Alternate Method

3y² + 3y + 4y + 4 = 0

∴ 3y(y + 1) + 4(y + 1) = 0

∴ (3y + 4) (y + 1) = 0

∴ y = -1 or y = −`4/3`

∴ y = `(-7+1)/6 or y = (−7-1)/6`

∴ y = -1 or y = -` 8/6= -4/3`

Is there an error in this question or solution?

Advertisement

Advertisement

Solve : 7y = -3y2 - 4 Concept: Roots of a Quadratic Equation.

Advertisement